ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI PENERAPAN AKUNTANSI BERBASIS AKRUAL PADA DINAS PARIWISATA DAN EKONOMI KREATIF PROVINSI NTT - Resvina Situmorang; Agustinus Beda Kewela; Irwan Irwan; Yunelci M. Seliamang (JAKA - Jurnal Jurusan Akuntasi, 2022)
This study aims to examine the extent of the influence of regulatory development on the application of accrual-based government accounting standards; the effect of information systems on the application of accrual-based government accounting standards; and the influence of the quality of human resources on the application of accrual-based government accounting standards. Especially at the works units and examine the various factors that exist at the tourism and creative economics department of east Nusa Tenggara province from human factors thought to have an influence on the level implementation of accrual accounting. The human factors include level of education employees, employees training and the quality of information technology. The data collected were processed using questionnaires and purposive sampling technique with the criteria of bachelor degree or associate degree, working above four years and permanent employees. A total of 67 samples using tolerance error 10 percent became 40 samples. The multiple data analysis technique using statistic application SPSS 25.0. The result of this study indicate that the implementation of accrual accounting at the tourism and creative economics department of east Nusa Tenggara province is still low. In Particular the implementation of accrual accounting is significantly affected by level of education employee, employees training and the quality of information technology